Perfect phrases for conflict resolution : hundreds of ready-to-use phrases for encouraging a more productive and efficient work environment - Polsky, Lawrence (Perfect phrases series., 2011)
THE RIGHT PHRASE FOR EVERY SITUATION . . . EVERY TIME Conflict in the workplace is inevitable. When you have the right words and phrases at your command, you can quickly resolve any disagreement-and prevent it from spreading into an uncontrollable fire. Perfect Phrases for Conflict Resolution has hundreds of ready-to-use phrases, dialogs, and practice scripts to help you rise above the conflict and focus on solving the problem, whether it's with an employee, boss, customer, supplier, or coworker. This handy, quick-reference guide provides effective language for dealing with: A micromanaging supervisor An underperforming employee A peer's disruptive work habits Unreasonable or unethical customer requests Abrupt, rude, and unprofessional coworkers.